Development of Solar Powered Intermittent Adsorption Refrigeration System - Chavda, Tilak V; Kumar, Naveen; Sreekumar, A (Journal of Agricultural Engineering, 2013)
A laboratory scale prototype of solar powered solid adsorption refrigeration system, using ammonia as refrigerant and barium chloride as absorbent was successfully developed and evaluated. The system consisted of a flat plate solar collector, condenser, liquid ammonia receiver, evaporator and connecting pipes without control valves. The system worked on day and night cycle, and required only solar energy for operation. It produced 1.40 kg ice per day per sq m collector area. The COP for the prototype was found to be around 0.045 during the month of February. Important reasons for low COP have been identified.